2006
DOI: 10.1007/s11430-006-0483-5
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal water storage change of the Yangtze River basin detected by GRACE

Abstract: US-Germany co-sponsered satellite gravimetry mission GRACE (Gravity Recovery And Climate Experiment), launched in March 2002, has been producing monthly time series of Earth gravity models up to degree and order of 120. The GRACE mission consists of two identical satellites flying on an almost polar orbit with an altitude of about 300-500 km and satelite-to-satellite ranging of about 220 km. Thanks to the payloads of space-borne GPS receivers, accelerometers and high-precision K-band satelite-to-satellite rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…3.2), and each column represents the difference between each time series and the reference. The covariance matrix S of the series of differences is computed as E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 0 4 ; 1 1 6 ; 3 7 5 S ¼ covðYÞ; (4) where covð•Þ is the covariance operator. A generic element of S represents either a variance estimate (for i ¼ j) or a covariance estimate (for i ≠ j).…”
Section: Three-cornered Hat Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3.2), and each column represents the difference between each time series and the reference. The covariance matrix S of the series of differences is computed as E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 0 4 ; 1 1 6 ; 3 7 5 S ¼ covðYÞ; (4) where covð•Þ is the covariance operator. A generic element of S represents either a variance estimate (for i ¼ j) or a covariance estimate (for i ≠ j).…”
Section: Three-cornered Hat Methodsmentioning
confidence: 99%
“…Yangtze, 4 Volta, 5 Nile, 6 and other river basins. Additional studies from GRACE are related to monitoring the groundwater withdrawal in India 7 and China, 8 contributions of glaciers and ice caps to sea-level rise, 9 and evaluation of naturally and anthropogenically induced variations in water availability in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…In China, GRACE data have been compared with several model simulations and used to extract TWS's spatial and temporal variation characteristics as well as its responses to droughts (Duan et al, 2007;Zhong et al, 2009;Wang and Yang, 2013;Hu et al, 2006;Xu et al, 2013;Tang et al, 2013Tang et al, , 2014. The serious TWS depletion in north China has gained much attention in recent years (Su et al, 2011;Moiwo et al, 2009;Feng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are ten years of useful and comparable data to analyze interannual (e.g., seasonal) and long-term (e.g., the mass loss in Greenland) changes in our climate system that allow for a better understanding of the global water cycle, and especially of droughts and floods. However, for direct basin (Rodell et al 2004b), the Yangtze river basin (Hu et al 2006), and the Zambezi river basin (Winsemius et al 2006), we can record a concentration on the Amazon river (see, e.g., Chen et al 2006, Chen et al 2009, Chen et al 2010, Fengler et al 2007, Syed et al 2005, Tapley et al 2004), which was observed for different periods of time with different techniques. The Amazon area is the largest water shed on Earth and, thus, has a major influence on the global climate, sea levels, and temperatures.…”
Section: Introductionmentioning
confidence: 86%